(untitled) (Bangladesh Medical Journal Khulna, 2020)
Background: Ponseti’s technique has become the standard and most effective treatment modality for correction of Congenital Talipes Equinovarus (CTEV) in newborn. With time, little modification has been done in the classic technique. Objective: Our objective in this study was to compare the outcome in the recent years (modified Ponseti technique) with the results of our previous study (classic Ponseti technique). Methods: A total number of 976 patients (1553 feet) of Congenital Talipes Equino Varus were treated from October 2009 to February 2019 in Khulna Medical College Hospital and in private hospitals. In this retrospective study (based on convenient sampling), there were two groups. In group A, a total 621 patients (with a total 1033 feet) were treated from October 2009 to August, 2015. In group B, 355 patients (520 feet) were treated from November 2015 to February 2019. Results: In this study, in group A, approximately 88.6% was in 0-6 months age group. 64.9% was male patients. 3.7% patients had positive family history. In group B, majority of the patients (301, 84.8%) was in 0-6 months age group. 211 patients (59.4%) was male child. In approximately 3.1% (11) patients family history was positive. Approximately in 95.9% (991 out of total 1033) and 96.5% (502 out of total 520) feet respectively in group A and B, tenotomy was required. Dropout rates were 7.6% and 4.1% in respective groups. Minor bleeding was observed in approximately 1.5% (15) and 1.4% (7) feet in respective groups, followed by plaster related complications in approximately 2.2% (23) and 1.0% (5) feet in group A and B. Patients’ compliance was found significantly higher in group B in contrast to group A. In group B, it was over 90%, whereas in group A, it was approximately 64.1 %. Conclusion: The ultimate outcome of Ponseti repair is improving by less requirement of total number of plaster, resistant cases and reduction in overall dropout rate by the newer modification. Bang Med J (Khulna) 2019; 52 : 7-11